ანტიკური კულტები საქართველოში (ათენა) - მშვილდაძე, მარიკა (My University, 2016)
Athena was honoured both, in Western and Eastern Georgia as seen in the artefacts. Mostly glyptical and numismatic monuments from Georgia show Athena. Urbnisi necropolis in Eastern Georgia renders 11 Roman Athena-type gemmas, the most prominent output for Georgia. One more gemma from Iberia (Eastern Georgia) is produced by famous craftsman. Golden ring with Athena-type oval garnet from the village Magraneti is produced by Hyllos from Alexandria, copying Athena Lemnis of Phidias. The chronological frames for the glyptic material with the depiction of Athena varies from B.C. 2nd to A.D. 3rd cc. which coincides with Hellinistic and Late Antique periods. According to our research, cult of Athena was very popular in Iberia of this period. Popularity of Athena’s cult in the capital city Mtskheta and in the one of the most important economic center, Urbnisi, is explained by the intensive cultural-economical contacts with the Eastern provinces of the Roman Empire. Athena was very popular among the aristocracy and within the common citizens as well. The depiction of Athena is common for the Georgian numismatics. The classic stater, which is known as starer of Aka in academic literature, is an example for this opinion.
ANTIQUE DEITIES IN GEORGIA (ATHENA)
https://geohistory.humanities.tsu.ge/ge/procedings/83-shromebi/165-shromebi-10.html
Keywords: ანტიკური კულტები; ათენა; ვანი; აკესი